SARS-CoV-2 Infection during the Omicron Surge among Patients Receiving Dialysis: The Role of Circulating Receptor-Binding Domain Antibodies and Vaccine Doses. Issue 10 (October 2022) - Montez-Rath, Maria E.; Garcia, Pablo; Han, Jialin; Cadden, LinaCel; Hunsader, Patti; Morgan, Curt; Kerschmann, Russell; Beyer, Paul; Dittrich, Mary; Block, Geoffrey A.; Parsonnet, Julie; Chertow, Glenn M.; et al.
Significance Statement: As the SARS-CoV-2 pandemic enters a potentially endemic phase, with fewer community-level mitigation approaches, clinical parameters that indicate heightened infection risk can guide targeted provision of additional vaccine doses, or other protective measures, among patients receiving dialysis. In our prospective cohort study of 3576 patients, three doses of mRNA vaccines enhanced protection against infection during the Omicron-dominant period in the United States. Irrespective of number of vaccine doses, however, patients with circulating receptor-binding domain semiquantitative index values <506 BAU/ml had a two- to three-fold higher risk for infection than patients with higher values. Low circulating antibody levels can inform need and timing of further vaccine doses or monoclonal antibodies to reduce risk for SARS-CoV-2 infection among patients receiving dialysis. Abstract : Background: It is unclear whether circulating antibody levels conferred protection against SARS-CoV-2 infection among patients receiving dialysis during the Omicron-dominant period. Methods: We followed monthly semiquantitative SARS-CoV-2 RBD IgG index values in a randomly selected nationwide cohort of patients receiving dialysis and ascertained SARS-CoV-2 infection during the Omicron-dominant period of December 25, 2021 to January 31, 2022 using electronic health records. We estimated the relative risk for documented SARS-CoV-2 infection by vaccination status and by circulating RBD IgG using a log-binomial model accounting for age, sex, and prior COVID-19. Results: Among 3576 patients receiving dialysis, 901 (25%) received a third mRNA vaccine dose as of December 24, 2021. Early antibody responses to third doses were robust (median peak index IgG value at assay limit of 150). During the Omicron-dominant period, SARS-CoV-2 infection was documented in 340 (7%) patients. Risk for infection was higher among patients without vaccination and with one to two doses (RR, 2.1; 95% CI, 1.6 to 2.8, and RR, 1.3; 95% CI, 1.0 to 1.8 versus three doses, respectively). Irrespective of the number of vaccine doses, risk for infection was higher among patients with circulating RBD IgG <23 (506 BAU/ml) (RR range, 2.1 to 3.2, 95% CI, 1.3 to 3.4 and 95% CI, 2.2 to 4.5, respectively) compared with RBD IgG ≥23. Conclusions: Among patients receiving dialysis, a third mRNA vaccine dose enhanced protection against SARS-CoV-2 infection during the Omicron-dominant period, but a low circulating RBD antibody response was associated with risk for infection independent of the number of vaccine doses. Measuring circulating antibody levels in this high-risk group could inform optimal timing of vaccination and other measures to reduce risk of SARS-CoV-2 infection.